If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 8x = x Combine like terms: 6x + 8x = 14x 14x = x Solving 14x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 14x + -1x = x + -1x Combine like terms: 14x + -1x = 13x 13x = x + -1x Combine like terms: x + -1x = 0 13x = 0 Divide each side by '13'. x = 0 Simplifying x = 0
| -9=x+12 | | 3x+5x-15=37 | | 7x+1=7x-x | | a(b-c)=d | | x+108=100 | | 8+4d=36 | | 18+108=126 | | 8+4d=37 | | z=6*3.14xy | | 2-11x=122+x | | 20+3n=-4 | | -9x-4=23 | | 13-7x=58-28x | | 3(z-5)+6z-1= | | 2x+2x-5=19 | | 10x-130=1 | | 6k-(3k-6)= | | 8-3y=-13 | | 4x+5=41 | | 2+5x=26+5x | | (n-9)*9=27 | | 3(5x-1)=60 | | 2x+7y=24 | | y/5=25 | | (n-3)*2=16 | | log(x-13)=1 | | 4a-3a-2=2(3a-2) | | 7x+17=8x+8 | | 5X+26=X+50 | | n*6=100 | | -5x-35=5 | | y--28=y*32 |